Elaboración de un folleto infográfico que involucre el estudio semiótico del danzante de Pujilí para utilidad del G.A.D. municipal en el período 2013 - Lidioma Escobar, Marcia Elizabeth (2015)
The present project has been developed following the investigation guidelines provided by the Technical University of Cotopaxi. Through of this investigation, we have realized an empirical semiotic study of the different pieces of clothing is part of typical costume Decentralized Autonomous Government of the Pujilí Canton “Danzante” character. The pieces of clothing were previously photographed in high quality. Each one of them was first illustrated and then located in the layout of the photographic pamphlet. This contains all the characteristics and the semiotic analysis. They were recollected during the investigation process. The aim of this investigation is to emphasize all the traditional features which grant the “Danzante” character a real cultural primacy in his own land and all over the world….